A comparative study of chlorhexidine-coated tulle gras versus polyurethane adhesive film for donor site wound dressing in split skin graft cases - Vhora, Paresh; Baviskar, Mayur G.; Vakil, Riya B. (International Journal of Research in Medical Sciences, 2024)
Background: Restoration of the skin barrier after wounding prevents infection, and minimises wound contraction, cosmetic disfigurement and volume depletion. Skin grafting represents an effective solution for large skin defects. Optimum care for donor-site wounds should promote wound healing cost-effectively while preventing complications like pain, infection, and scarring. Healthcare professionals use various dressings and topical agents, but there is no ideal dressing. In our study, we aim to compare the efficacy of chlorhexidine coated tulle gras (CTG) and polyurethane adhesive film (Opsite) in managing donor site wounds in split skin grafts. Methods: This study was conducted at the Department of Surgery, Lokmanya Tilak Municipal Medical College, a teaching hospital and tertiary care centre in Mumbai, from September 2012 to December 2014, following a prospective observational design, with a sample size of 50 patients. Results: The study subjects were predominantly in the 20-30 age group (36.0%) and mostly male (72.0%). The Opsite group reported significantly higher comfort scores (56.0%) compared to the CTG group (36.0%, p=0.002). Healing time was significantly shorter in the Opsite group (7.36±0.7 days) compared to the CTG group (9.52±1.39 days, p=0.001). Pain scores were significantly lower in the Opsite group at all observed times. Deviations like soakage and slippage were frequent in the Opsite group (76.0% and 56.0%, respectively). Conclusions: Opsite has advantages over CTG viz. faster healing and re-epithelization, decreased pain, and greater comfort. However, soakage and exudate formation are seen with Opsite.